2008
DOI: 10.1007/s00436-008-1240-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of indigenous plant extracts against larvae of Culex quinquefasciatus Say (Diptera: Culicidae)

Abstract: This study investigates the larvicidal potential of indigenous plant extracts from commonly used medicinal herbs as an environmentally safe measure to control the filarial vector, Culex quinquefasciatus Say (Diptera: Culicidae). The early fourth-instar larvae of C. quinquefasciatus, reared in the laboratory, were used for larvicidal assay with water, hot water, acetone, chloroform, and methanol leaf, stem-bark, and flower extracts of Acacia arabica Willd. Sans, Cedrus deodara Roxb, Hibiscus rosa-sinensis L., M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(34 citation statements)
references
References 36 publications
1
31
0
2
Order By: Relevance
“…Moreover, the direct proportion detected between the mortality means and exposure time from 24 to 48 h confirmed what has been reported by several investigators (Abdul Rahuman et al, 2008;Abdu Zahir et al, 2009), which showed gradual buildup in mortalities in relation to time factor post treatments.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the direct proportion detected between the mortality means and exposure time from 24 to 48 h confirmed what has been reported by several investigators (Abdul Rahuman et al, 2008;Abdu Zahir et al, 2009), which showed gradual buildup in mortalities in relation to time factor post treatments.…”
Section: Discussionsupporting
confidence: 90%
“…Similarlyin this study, has the concentration of extract increases from 1000 ppm to 5000 ppm, the percentage mortality also increases almost five fold, from initial concentration to final concentration. Several investigators also confirmed positive relationship between larval mortality and time factor [36][37][38][39]. As the time of exposure increases, the percentage larval mortality of 3 instar An.…”
Section: Discussionmentioning
confidence: 75%
“…This warrants the need for the development of new strategies for selective control of mosquito populations. Plants are a good source of alternative agents for control of mosquitoes [13,14] because they are rich in bioactive chemicals which are biodegradable. The Euphorbia genus is known to contain a wide variety of terpenoids, ranging from mono-, sesqui-and diterpenes to triterpenoids, flavonoids and steroids known for their toxicity or potential therapeutic activity [15].…”
Section: Chemical Composition and Mosquitocidal Activity Of N-hexane mentioning
confidence: 99%